Biomaterials and Medical Devices A Perspective from an Emerging Country - Mahyudin, Ferdyansyah; Hermawan, Hendra (Advanced Structured Materials,, 2016)
This book presents an introduction to biomaterials with the focus on the current development and future direction of biomaterials and medical devices research and development in Indonesia. It is the first biomaterials book written by selected academic and clinical experts experts on biomaterials and medical devices from various institutions and industries in Indonesia. It serves as a reference source for researchers starting new projects, for companies developing and marketing products and for governments setting new policies. Chapter one covers the fundamentals of biomaterials, types of biomaterials, their structures and properties and the relationship between them. Chapter two discusses unconventional processing of biomaterials including nano-hybrid organic-inorganic biomaterials. Chapter three addresses biocompatibility issues including in vitro cytotoxicity, genotoxicity, in vitro cell models, biocompatibility data and its related failure. Chapter four describes degradable biomaterial for medical implants, which include biodegradable polymers, biodegradable metals, degradation assessment techniques and future directions. Chapter five focuses on animal models for biomaterial research, ethics, care and use, implantation study and monitoring and studies on medical implants in animals in Indonesia. Chapter six covers biomimetic bioceramics, natural-based biocomposites and the latest research on natural-based biomaterials in Indonesia. Chapter seven describes recent advances in natural biomaterial from human and animal tissue, its processing and applications. Chapter eight discusses orthopedic applications of biomaterials focusing on most common problems in Indonesia, and surgical intervention and implants. Chapter nine describes biomaterials in dentistry and their development in Indonesia.